Policy Dilemmas in Financing Long‐term Care in Europe. (22nd December 2016) - Costa‐Font, Joan; Courbage, Christophe; Zweifel, Peter
Abstract: Long‐term care (LTC) is the largest insurable risk facing the elderly in most high‐income countries. Paradoxically, institutional responses to the need to insure ex ante (i.e. before the contingency occurs) the financial risks of needing LTC, either through social, private, or self insurance, exhibit limited development. In contrast, mechanisms to finance LTC ex post continue to develop, primarily those supported by the public sector (i.e. subsidies or tax deductions) and the family (i.e. intergenerational transfers). Both ex ante and ex post types of financing mechanisms are found to be subject to shortcomings which give rise to dilemmas for public policy. Governments confront these dilemmas in different ways, causing a great deal of heterogeneity in the financing and provision of LTC services across Europe. Abstract : LTC finance needs to be considered as part of an overall retirement strategy rather than as a simple extension of health insurance, even if one can separate the goals of consumption smoothing (i.e. retirement) from insurance (i.e. LTC).